Understanding on the Problem of ‘Harijan’ In India: Intersectionality and Social Exclusion: Understanding the Plight of Harijan Women in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This report develops an understanding on the problem of“Harijan ’ in India. Harijan  include asection of  in Indian society, who comefrom the lower castes, particularly the untouchable and other lower caste, andwho beside gender discrimination, also suffered from the prescribed customaryprovisions in the institution of caste and untouchability. Excluded  are not 'just like' the rest of the . Theyare also disadvantaged by who they are.They suffer from social exclusion which deprives them of choices andopportunities to escape from poverty and denies them a voice to claim theirrights. There is a close inter-face between patriarchy and social exclusionwhich enforce each other. The  fromdiscriminated groups suffer from triple deprivation – gender, poverty andsocial exclusion. The discussion presented selected evidence on the nature andforms of caste – based discrimination suffered by Harijan  in access to sources of livelihood and socialneeds. This evidence however, is very limited and there is a need to study thenature and forms of discrimination faced by Harijan  as a woman, as a Harijan woman and as poor .The Harijan woman’s exclusion from the rights normally considered as accruingto every Indian citizen thus needs to be examined more closely, looking both ather conditions of livelihood and employment and the various ways in which sheis subjugated in the public and private spheres. The challenge is to capturethe interface of these three dimensions of caste, class and gender and toanalyse the consequences of social exclusion and discrimination on their rightsand citizenship. This would help to conceptualize inclusive policies to addressthe problems of Harijan  moreeffectively.